Neumoconiosis en la minería subterránea del carbón, Amaga, 1995 (1997)
ABSTRACT: A prevalence poll was made to stablish of pneumoconiosis in a representative sample of miners of charcoal in Amagá, Antioquia, Colombia. Likewise, the statistical association among some occupationals risk factors and pneumoconiosis was studied. The prevalence for pneumoconiosis was 5.12 * 10(2). High prevalence were found among workers in mechanized and mixed mines, 6.3 and 5.9 * 10(2), respectively, but the differences weren't significatives to compared with the prevalence among handle mines workers. 82% of the population have beeen working more than five years in high and moderate risk mines. The prevalence for occupation of high and middle exposition vary between 5.6 * 10(2) and 6.25 * 10(2). Multivariate analysis showes that working in mechanize or mixed mine, age, brinchitis and chest trauma is predictors of frequency of pneumoconiosis.